Pemberdayaan Petani dalam Memanfaatkan Air Hujan untuk Sistem Budidaya Tanaman dengan Metode Water Harvesting - Tuhuteru, Sumiyati; Mahanani , Anti Uni; Rumbiak , Rein Edward Yohanes; Dewi, Yohana Sutiknyawati Kusuma; Tulak, Alber; Tabuni, Endius; Tabo, Opapur; Doga, Konius; Wenda, Endison; Lengka, Mariana; Himan, Rusina (Warta LPM, 2023)
Rainwater harvesting is one municipal initiative that uses rainwater for everyday needs. Rainwater is very useful in meeting water sources for agriculture, homes and industries, but unmanaged rainwater can also cause disasters such as flooding and flooding. The rainwater that falls on the earth is clean water for living things. However, during the rainy season, when the catchment area decreases, rainwater cannot penetrate into the ground and often causes flooding. For this reason, this service activity is essential to help farmers meet their crops' water needs during periods of drought. This activity was conducted from November to December 2022 in Husok Village, Hubikiak District, Jayawijaya District, Papua Mountains. The implementation of this service activity will be implemented through the pilot project phase of the Kosabangsa program. This stage is divided into his three phases: the preparation phase, the activity phase, and the evaluation and monitoring phase. The results of the implementation of this community service activity were achieved based on the plans set and the tools made to function properly because they can accommodate and drain water to each holding tank in the middle of the land for watering the plants as well as being an alternative in providing clean water for farmer groups so they no longer have to walk far to take clean water. This is supported by community participation in accepting the technology made by the implementing team.